2019
DOI: 10.1039/c9sm01185d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of negative membrane curvature sensing and generation by I-BARs in filopodia of living cells

Abstract: We analyze diffraction-limited filopodia of living cells to quantify negative curvature sensing and generation for two prototypic I-BAR domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Interestingly, a recent work described how ezrin needs to act in partnership with the I-BAR protein IRSp53 to enrich in negatively curved membranes (43). Previous work done on IRSp53 has related this protein to PM ruffling (44,45), filopodia formation (46)(47)(48)(49) and endocytosis (50), but, so far, no mechanosensing mechanism relying on its capacity to bind negatively-curved membranes has been described. Moreover, recent studies in vitro and in vivo have pointed out that the I-BAR domain of IRSp53 displays a peak of sorting at evaginations with curvatures of 0.05 nm -1 , and that lower curvature values comparable to the ones obtained by TEM imaging of our evaginations also led to a two-fold enrichment of this domain with respect to a control membrane marker (47,51).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent work described how ezrin needs to act in partnership with the I-BAR protein IRSp53 to enrich in negatively curved membranes (43). Previous work done on IRSp53 has related this protein to PM ruffling (44,45), filopodia formation (46)(47)(48)(49) and endocytosis (50), but, so far, no mechanosensing mechanism relying on its capacity to bind negatively-curved membranes has been described. Moreover, recent studies in vitro and in vivo have pointed out that the I-BAR domain of IRSp53 displays a peak of sorting at evaginations with curvatures of 0.05 nm -1 , and that lower curvature values comparable to the ones obtained by TEM imaging of our evaginations also led to a two-fold enrichment of this domain with respect to a control membrane marker (47,51).…”
Section: Resultsmentioning
confidence: 99%
“…The curvature mismatch model was first developed by Kralj-Iglic et al to describe the protein distribution coupled to cell shape 61 , and later to account for other experimental observations of curvature-dependent protein sorting in reconstituted systems and in living cells 46,50,62 . At the molecular scale, protein-membrane binding involves either the deformation of the protein-bound membrane due to the intrinsic curvature of the bound proteins or the deformation 6 of the bound-protein due to the membrane curvature, or a combination of both.…”
Section: Curvature Mismatch Modelmentioning
confidence: 99%
“…Indeed, it has been shown that the classical BAR domains prefer to associate with membranes with a positive curvature [42][43][44][45] , while I-BAR domain prefers to bind to membranes with a negative curvature 46 . Emerging cell biology studies have shown that the curvature sensing ability of BAR proteins contributes to their cellular localization and consequently their cellular functions [47][48][49][50] . To reveal physical mechanisms by which BAR proteins sense membrane curvature, computer simulations, theoretical modeling and in vitro reconstitution systems have been developed 6,10,50 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pulling tubes from a GUV with encapsulated peptides provided a way to determine the preference of the IRSp53 I-BAR domain for ~18 nm radius 19 . More recently, a novel method utilizing protein sorting on tubular filopodia of varying diameter showed preferential binding to 25-nm and 19-nm radii for MIM I-BAR and IRSp53, respectively 20 . Computer simulations could provide insights but are limited by the system size and computational resources.…”
mentioning
confidence: 99%